Identifikasi Koleksi Museum Perjuangan Subkoss Garuda Sriwijaya Lubuklinggau Sebagai Sumber Belajar Bagi Masyarakat - Isbandiyah Isbandiyah; Supriyanto Supriyanto (LP4MK STKIP PGRI Lubuklinggau, 2026)
This study aimed to identify and describe the Subkoss Museum of Lubuklinggau as a learning resource for the community. The research employed a qualitative method with a descriptive approach. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Data validity was ensured through triangulation techniques. The findings revealed that: (1) the Subkoss Garuda Sriwijaya Struggle Museum of Lubuklinggau possesses 140 collections that can be utilized as learning resources for the community; (2) the museum serves as a learning resource because it functions as a repository of the nation's history, particularly concerning past events related to the struggle of the people of Lubuklinggau and, more broadly, the people of South Sumatra in defending their region against colonialism and fighting for national independence. In history education, museums are among the most appropriate places to obtain historical information and to enhance public understanding of historical events, especially for students; and (3) all collections housed in the museum can serve as learning resources for various educational levels. The main distinction between early childhood education and higher education lies in the way museum educators deliver and explain the collections to visitors. Keywords: Museum Collections, Learning Resources, Community.